Risk Mitigation Strategy for Spend Management in Strategic Procurement Through Automation of Processes - Layaq, Mian Wasim; Goudz, Alexander; Noche, Bernd (ExcelingTech, 2020)
The digital revolution is currently shaking every sector of the industry especially the supply chain and procurement industry. Concepts like â€œIoTâ€, â€œIndustry 4.0â€ and â€œProcurement 4.0â€ are floating all around which is making the industry more competitive. The digital revolution is compelling the businesses to work in collaboration to achieve their targets because it is getting almost impossible for companies to survive independently, while on the other hand these collaboration lead to the complexities of the processes which can result in-transparencies in the process flows and spend management. A proper, clear and transparent spend management is the key to the success of any organization and an uncontrolled, unclear spend management can lead the companies to bankruptcies. The purpose of this research paper is to show how strategic procurement perform their spend management with conventional methods? and how the digitization and automation concepts can be used to improve the whole spend management process and how to mitigate the risks associated with spend management? Emerging literature, case studies, blogs, expert opinions, market knowledge, practical business experiences and citations are used to fulfill this task.